Quels indicateurs de développement professionnel en formation technologique supérieure ? - Raquel Becerril Ortega; Bernard Fraysse (Université de Provence, 2009)
The article proposes an indicator which measures the reciprocal relationship between graduate studies in technology and the professional world. The chosen theoretical framework conceives professional activity as a source of professional competence development. The results of the analysis show that there are different ways of managing the classroom coactivity between the teacher and the students which are related to professional development and students' profile.